Evaluating Breast Self-examination Awareness Among Young Adult Women in Vaniyamkulam Panchayat to Create an Educational Booklet - Danababy; Lt Col Regina P.F.; Rasna K.P.; Reshma M.; Sabitha Sibi; Sandramol S.; Shabnam (International Journal of Oncological Nursing and Practices, 2024)
Introduction: Breast cancer ranks as the second most prevalent cancer worldwide and stands as the primary cancer type among women, both in developed and developing nations. It is estimated that around 25% of all cancer cases globally are attributed to breast cancer. Notably, there was a significant increase in breast cancer incidence from 2008 to 2012 on a global scale. Methods: The research utilized a quantitative methodology, employing a descriptive study design. A purposive sampling method was utilized to carefully select 50 participants for the study. Data collection involved demographic variables and a semi-structured questionnaire. The study was conducted on December 14, 2023, and data analysis utilized both descriptive and inferential statistics. Results: As we have assessed the level of knowledge regarding breast self-examination among early adulthood women in selected settings of Vaniyamkulam Panchayat, about 4 (8%) samples have adequate knowledge, 21 (42%) have moderate knowledge, 25 (50%) samples have inadequate knowledge about breast self-examination. Conclusion: The result obtained after the analysis found that knowledge regarding breast self-examination among early adulthood women of Vaniyamkulam Panchayat, revealed that maximum women had inadequate knowledge. Hence the researchers prepared an information booklet and distributed among the participants, anticipating that their knowledge about breast self-examination will be improved.
Keywords: Breast self-examination; Knowledge; breast cancer; demographic variables; descriptive and inferential statistics